Lipoarabinomannan as a Point-of-Care Assay for Diagnosis of Tuberculosis: How Far Are We to Use It? - Flores, Julio; Cancino, Juan Carlos; Chavez-Galan, Leslie (Frontiers in Microbiology, 2021)
Tuberculosis (TB) is still a severe public health problem, the current diagnostic tests have limitations, and it delays the treatment initiation. Lipoarabinomannan (LAM) is a glycolipid, which is a component of the cell wall of the bacillus Mycobacterium tuberculosis, the etiologic agent of TB; this glycolipid is excreted as a soluble form in the urine. The World Health Organization established that the design of new TB diagnostic methods is one of the priorities of action in the EndTB Strategy. LAM is considered a biomarker and has been suggested to develop diagnostic tests based on the identification of LAM in urine, and it is one of the most prominent candidates to develop point-of-care diagnostic test because the urine is an easily collected sample. Moreover, LAM can regulate the immune response in the host. LAM could also be found in the serum of TB patients, where it probably affects a wide variety of cell populations. Consequently, it could influence the quality of both the innate and the adaptive immune responses during TB. Here, we revised the evidence that supports that LAM could be used as a tool for the development of new point-of-care tests for TB diagnosis, and we discussed the mechanisms that could be contributing to the low sensibility of diagnostic testing.